2007
DOI: 10.1037/0096-1523.33.3.743
|View full text |Cite
|
Sign up to set email alerts
|

Tone sequences with conflicting fundamental pitch and timbre changes are heard differently by musicians and nonmusicians.

Abstract: An Auditory Ambiguity Test (AAT) was taken twice by nonmusicians, musical amateurs, and professional musicians. The AAT comprised different tone pairs, presented in both within-pair orders, in which overtone spectra rising in pitch were associated with missing fundamental frequencies (F0) falling in pitch, and vice versa. The F0 interval ranged from 2 to 9 semitones. The participants were instructed to decide whether the perceived pitch went up or down; no information was provided on the ambiguity of the stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 21 publications
8
55
0
3
Order By: Relevance
“…Our method of interleaving two independent tracks, with either consistent or inconsistent changes in F0 and spectrum, provides a way of assessing the effects of timbre on judgments both at a group and an individual level. This in turn provides a method to evaluate individual differences in the dominance of "spectral" vs. "periodicity" pitch in a more nuanced way than has been possible in earlier studies ͑Laguitton et al, 1998;Schneider et al, 2005;Seither-Preisler et al, 2007͒. These findings, which provide clear evidence that DLCs for complex tones with corresponding components effectively measure residue-pitch discrimination, have direct practical implications for pitch-perception researchers, as they validate DLF0s as a measure of residue-pitch discriminability and pitch strength. Moreover, the findings confirm and quantify the influence of randomizing the lowest harmonic number across intervals ͑within trials͒, and they indicate that although perhaps not absolutely necessary, when applied properly, such randomization reduces the influence of timbre or other cues related to changes in the frequency of the lowest harmonic-but unrelated to residue-pitch perception.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our method of interleaving two independent tracks, with either consistent or inconsistent changes in F0 and spectrum, provides a way of assessing the effects of timbre on judgments both at a group and an individual level. This in turn provides a method to evaluate individual differences in the dominance of "spectral" vs. "periodicity" pitch in a more nuanced way than has been possible in earlier studies ͑Laguitton et al, 1998;Schneider et al, 2005;Seither-Preisler et al, 2007͒. These findings, which provide clear evidence that DLCs for complex tones with corresponding components effectively measure residue-pitch discrimination, have direct practical implications for pitch-perception researchers, as they validate DLF0s as a measure of residue-pitch discriminability and pitch strength. Moreover, the findings confirm and quantify the influence of randomizing the lowest harmonic number across intervals ͑within trials͒, and they indicate that although perhaps not absolutely necessary, when applied properly, such randomization reduces the influence of timbre or other cues related to changes in the frequency of the lowest harmonic-but unrelated to residue-pitch perception.…”
Section: Discussionmentioning
confidence: 64%
“…Although the two procedures yield similar estimates of DLC, the dual-track procedure that was used in Experiment 1 provides more information than the singletrack procedure, because it allows the extent to which the listener's responses were influenced by timbre or lowestharmonic number cues to be assessed, both on the level of individual listeners and on the level of the group data. Future studies could use this technique to estimate the relative weight assigned to F0 and spectrum by individual listeners in the absence of feedback in a more precise way than has been done in previous studies ͑e.g., Laguitton et al, 1998;Schneider et al, 2005;Seither-Preisler et al, 2007͒. Taken together, the results from experiments 1 and 2 suggest that DLCs are influenced by the harmonicity of the components in the complex. However, it could be argued that our paradigm, which involved roving the lowest harmonic number and providing feedback based on the F0, may have forced listeners to use residue pitch cues more than would be normally done in situations where there are no timbral or spectral differences between the comparison tones.…”
Section: B Results and Discussionmentioning
confidence: 74%
“…It is not surprising that musically trained adults' pitch perception would be less influenced by spectral variation. For example, Seither-Preisler et al (2007) showed that compared to nonmusicians, musicians are more likely to perceive harmonic complexes on the basis of pitch as opposed to timbre.…”
Section: Discussionmentioning
confidence: 99%
“…A particularly instructive demonstration of this is owing to Seither-Preisler et al (2007), whose experiment has some design similarities with London's study. Just as London included rhythm pairs in which the rhythm with the slower nominal tactus tempo had a faster "surface rate of motion," SeitherPreisler et al presented pairs of tones in which the tone with the lower pitch had a brighter timbre.…”
Section: An Analogy With Pitch and Timbre Perceptionmentioning
confidence: 93%